REINTERPRETING PAST, PRESENT, AND FUTURE REGARDING ORGANIZATION’S STRATEGIC AGENTS PERCEPTION FROM PSYCHOLOGY AND NEUROSCIENCE - Guedes de Nonohay, Roberto; Ávila Pedrozo, Eugênio (Revista Sociais e Humanas, 2020)
Different perceptions of strategic agents in organizations can cause problems and opportunities. There is, therefore, the need to explore what may be the factors that can influence the formation of the perceptions of the strategic agents. We seek to explore the contemporary knowledge of psychology, based on a social rationality rather than economic. The brain, an important factor in social relation, is the locus of formation of the relation between past, present and future events. The objective of this essay is to propose a perspective for the analysis of the differences of the perceptions of the individuals in the organizations based on the psychology associated with a basic social logic of the functioning of the brain (social brain). The relationships between these time periods form the perceptions of the strategic agents in the moments in which they are and are in constant feedback, according to the results of the current perceptions. The contributions to the theory are in the integration of theories that can aid the study of the perception of the strategic agents. For management practice, this view is expected to contribute to the process of interpersonal relationship between employees and to facilitate the decision-making processes in organizations.